DSP based current controlled single stage single phase integrated converter with external compensating signal for Class-C & Class-D appliances. Issue 1 (1st January 2017) - Subbarao, Mopidevi; Sai Babu, Ch.; Satyanarayana, S.
Abstract: Design and implementation of a current controlled single stage single phase integrated AC/DC isolated Power Factor Correction (PFC) converter is presented in this paper. With the integrated topology reduces the number control switches. The proposed converter has the advantage of low bulk capacitor voltage and only single control switch hence reduce in complexity in control and cost. Sub-harmonic oscillations which are produced in conventional current controller. By adding an external compensating signal effect of oscillations are reduced and performance of the converter is improved. The proposed scheme is implemented in real time by TMS320F2812 digital signal processor (DSP) board. The performance of converter is verified both experimentally and by simulation at different load and line conditions. The proposed converter is designed for 90–230 V, 50 Hz AC input, 48 V DC output and operating at 100 kHz switching frequency. The Experimental results shows that the DSP-based fuzzy controlled single phase single switch integrated PFC converter achieve high power factor and satisfies IEC-61000-3-2 and other European input current harmonic limits for Class-C & Class-D applications.